Social Security : the Unfinished Work. - Blahous, Charles (Hoover Institution Press, 2010)
Arguing that an equitable Social Security solution will be unattainable unless we bring stakeholders together around a common understanding of the facts and of the need to take action to address them, former White House adviser Charles Blahous presents some often misunderstood, basic factual background about Social Security. He discusses how it affects program participants and explains the true demographic, economic, and political factors that threaten its future efficacy.